Understanding and awareness of taking takaful at a young age: a study among former sixth form students of SMKA Naim Lilbanat / Siti Fairuz Sujak, Syazwani Abd Rahim, Nurul Alya Zamri, Noraishah P. Othman and Rohaya Sulaiman - Sujak, Siti Fairuz; Abd Rahim, Syazwani; Zamri, Nurul Alya; P. Othman, Noraishah; Sulaiman, Rohaya (UiTM Cawangan Johor, 2025)
Takafid protection plans have expanded fast and are more popular than conventional insurance plans due to the community's demand and awareness. The reason is that the operations in Takaful are fully Shariah compliant. However, there are still groups, especially young people, who think the Takaful protection plan is unimportant in their lives because they lack an in-depth understanding and awareness of Takafitl and knowledge regarding the advantages of Takaji.ll compared to insurance. The objectives of this research are: First, to identify the level of understanding; Second, to identify the level of awareness; Third, to identify the level of knowledge of former sixth-form students of SlavKA Nairn Lilbanat regarding the advantages of Takaful compared to conventional insurance. This quantitative research methodology uses an online survey through a questionnaire to eighty respondents. The data that has been obtained 111 ill be analysed using SPSS Version 27. In this research, descriptive analysis and reliability analysis were performed. Findings from this research showed that the level of understanding and awareness of taking Takaful at a young age among respondents is high. The level of knowledge regarding the advantages of Takaful compared to insurance is also high and good. Finally, it is hoped that this finding can contribute to the parties involved, i.e. industry players, society, and future research. Therefore, it is suggested that future researchers do research related to awareness and understanding of Takaful among non-Muslims. Keywords: Takaful, Understanding, Awareness, Knowledge, Young age